MIXED CONVECTION OF NANOFLUID OVER A BACKWARD FACING STEP UNDER THE EFFECTS OF A TRIANGULAR OBSTACLE AND INCLINED MAGNETIC FIELD - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Begell House Inc, 2018)
In this study, laminar mixed convection of CuO-water nanofluid over a backward facing step with the presence of a triangular obstacle and under the effect of magnetic field was numerically investigated. Finite volume method was used to solve the governing equations for the range of parameters: Richardson number (between 0.01 and 100), Hartmann number (between 0 and 50), nanoparticle volume fraction (between 0 and 0.04), and horizontal location of the triangular obstacle (between 0.5H and 2H). It was observed that average heat transfer is a decreasing function of Richardson number and an increasing function of nanoparticle volume fraction. The dependence of average heat transfer on the magnetic field parameters shows a resonant-type behavior. The obstacle affects the local Nusselt number distribution near the step especially for lower values of Richardson number and Hartmann number. Artificial neural networks were used to develop models that can be used instead of high-fidelity computational fluid dynamics simulations for fast and accurate thermal performance predictions of the considered system.
Keywords: mixed convection; magneto hydrodynamics; nanofluid; obstacle; artificial neural networks